2016
DOI: 10.1177/2158244016643748
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Adherence and Quality of Life in Diabetes Mellitus Patients in Indonesia

Abstract: Adherence to treatment of diabetes mellitus (DM) can support successful therapy due to drug consumption over longtime periods. The objectives of this study are to evaluate the treatment adherence in DM as related to the quality of life and to evaluate factors associated with adherence and quality of life. This study used the Brief Medication Questionnaire (BMQ) to measure patients’ adherence. The Diabetes Quality of Life Clinical Trial Questionnaire (DQLCTQ) was used to measure patients’ quality of life. Subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
24
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 24 publications
8
24
1
5
Order By: Relevance
“…In line to our study results, medication adherence was reported as a predicting factor towards HRQoL [3538]. On the contrary, negative association between medication adherence and HRQoL was also reported in the literature [39, 40].…”
Section: Discussionsupporting
confidence: 92%
“…In line to our study results, medication adherence was reported as a predicting factor towards HRQoL [3538]. On the contrary, negative association between medication adherence and HRQoL was also reported in the literature [39, 40].…”
Section: Discussionsupporting
confidence: 92%
“…A previous study showed that demographic factors, psychological, social support; health care providers; medical systems; disease; and treatment-related factors can promote diabetic patients' adherence [12]. The results of the previous study are out line with our study, which showed that the sex and age of patients may influence patients' adherence and quality of life.…”
Section: Discussionsupporting
confidence: 89%
“…This questionnaire is widely used in Indonesia, even in the clinical trial study to observe QoL as the outcome or in the observational study. 17 Demographic data of the patients were collected from the questionnaire.…”
Section: Methodsmentioning
confidence: 99%